Existence of Periodic Fixed Point Theorems in the Setting of Generalized Quasi-Metric Spaces - Chi-Ming Chen; Erdal Karapınar; Vladimir Rakočević (Journal of Applied Mathematics)
We introduce the notions of (α-ϕ-ψ)-weaker Meir-Keeler contractive mappings and (α-φ)-stronger Meir-Keeler contractive mappings. We discuss the existence of periodic points in the setting of generalized quasi-metric spaces. Our results improve, extend, and generalize several results in the literature.